Factors Influencing The Development Of Lifelong Learning Skills: OUM Tracer Study - Latifah Abdol Latif; Mansor Fadzil; Norlia Goolamally (2012)

(untitled)
Emerging results of a tracer study conducted at Open University Malaysia (OUM) revealed that the four aspects, namely curriculum design, assessment system, teaching and learning and facilities provided by the university are significant factors contributing to the development of lifelong learning skills. The four predictor model explains 41.1% of the variance in the development of lifelong learning skills; this implies that there are other contributing factors which have not been included in this study. Among others, OUM needs to collaborate with employers to align its programmes’ curriculum design with the requirements of the workplace; to encourage use of open learning and flexible delivery in its teaching and learning; to practice assessment which evaluates what rather than how much has been learned; which stresses timely constructive feedback that results in congruence between course aims and learning outcomes. Computer-based facilities including the digital library help the institution to produce graduates who are equipped with lifelong learning skills. (Abstract by authors)